Effects of three different probiotics of Tibetan sheep origin and their complex probiotics on intestinal damage, immunity, and immune signaling pathways of mice infected with Clostridium perfringens type C - He, Xi; Ye, Guisheng; Xu, Shuqin; Chen, Xiaohui; He, Xiaolong; Gong, Zifeng (Frontiers in Microbiology, 2023)
Tibetan sheep have unique intestinal microorganisms in their intestines that are adapted to the highland alpine and anoxic environment. To further clarify the probiotic properties of Tibetan sheep-derived probiotics, we selected three Tibetan sheep-derived probiotic isolates (Enterococcus faecalis EF1-mh, Bacillus subtilis BS1-ql, and Lactobacillus sakei LS-ql) to investigate the protective mechanisms of monocultures and their complex strains against Clostridium perfringens type C infection in mice. We established a model of C. perfringens type C infection and used histology and molecular biology to analyze the effects and mechanisms of different probiotic treatments on mice after C. perfringens type C infection. After supplementation with either probiotics or complex probiotics, mice were improved in terms of weight reduction and reduced the levels of cytokines in serum and increased the levels of intestinal sIgA, and supplementation with complex probiotics was effective. In addition, both probiotic and complex probiotic supplementation effectively improved the damage of intestinal mucosa and spleen tissue. The relative expressions of Muc 2, Claudin-1, and Occludin genes were increased in the ileum. The three probiotics and the compound probiotics treatment significantly reduced the relative mRNA expression of toll-like/MyD88/NF-κB/MAPK. The effect of probiotic treatment was similar to the results of engramycin treatment, but the effect of engramycin treatment on intestinal sIgA was not significant. Our results clarify the immunomodulatory effects of the three probiotic isolates and the complex probiotics on C. perfringens infection, and the repair of the intestinal mucosal barrier.